2011
DOI: 10.1002/anie.201101842
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Enantioselective Total Synthesis of (+)‐Liphagal

Abstract: Ring a ding: The first catalytic enantioselective total synthesis of the meroterpenoid natural product (+)-liphagal is disclosed. The approach showcases a variety of technology including enantioselective enolate alkylation, a photochemical alkyne-alkene [2+2] reaction, microwave-assisted metal catalysis, and an intramolecular aryne capture cyclization reaction. Pivotal to the successful completion of the synthesis was a sequence involving ring expansion from a [6-5-4] tricycle to a [6-7] bicyclic core followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 69 publications
1
39
0
Order By: Relevance
“…Scheme 27) by the Stoltz group. 17 Among them, the biomimetic ring expansion approach provides novel methodologies to construct the requisite tetracyclic core structures in a shorter number of steps with higher overall yields. Especially, the George's approach (2015), 11 which involves the direct conversion of siphonodictyal B into liphagal (cf.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scheme 27) by the Stoltz group. 17 Among them, the biomimetic ring expansion approach provides novel methodologies to construct the requisite tetracyclic core structures in a shorter number of steps with higher overall yields. Especially, the George's approach (2015), 11 which involves the direct conversion of siphonodictyal B into liphagal (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Biosynthesis of corallidictyals A (3) and B (4) proposed by George et al 12 The unique structural features, attractive biological activities, limited availability from natural resources, and plausible biosynthetic pathway have made liphagal (1) an exceptionally intriguing and timely target for total synthesis. In 2006, the first total synthesis of racemic (±)-1 was presented by Andersen et al 6 Subsequently, the formal total syntheses of (±)-1 were reported by Mehta et al (2009) 13 and Kumar et al (2011), 17 and our group (2014). 18 Recently, the formal total synthesis of (±)-1 was reported by Ferreira et al (2017).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…( S )-L1 and ( S )-L2 ˙, Figure 1) enable the formation of the corresponding products with the best enantiomeric and diastereomeric ratios. Although ( R )- t -BuPHOX has been employed in natural product synthesis 15 and explored in transition-metal catalyzed allylic alkylations, 10a,16 these examples are quite rare considering the nearly prohibitive cost of the requisite starting material for ligand synthesis, ( R )- t -leucine. 17 Previously, 5,5-geminally disubstituted ( R )-valine-derived PHOX ligands (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Standard Tsuji–Wacker oxidation of enone 8 using PdCl 2 and CuCl under an atmosphere of oxygen generated the desired ketone, 13 which subsequently underwent an aldol condensation to provide dienone 12 in good yield (76% yield over 2 steps). 14 Enone 12 was then selectively mono-brominated to form vinyl bromide 7 in 83% yield on gram scale. 15 The cross coupling of 6 16 and 7 was next evaluated for optimal reaction conditions.…”
mentioning
confidence: 99%